Using Evidence and Data to Design an Intervention in the Project Community Model for Fostering Health and Wellbeing Among Adolescent Mothers and Their Children - Dzabala, Nettie; Kachingwe, Mtisunge; Chikowe, Ibrahim; Chidandale, Carol; van der Haar, Lotte (Frontiers in Public Health, 2021)
In this paper, quantitative and qualitative measurements of maternal psychosocial wellbeing were utilized in three districts in Malawi that guided decision-making to increase the wellbeing of adolescent mothers and promote the healthy upbringing of their children. The 1-year design stage of the study relied on several sources of information: literature search, prior project implementation of similar projects, discussions with officials at the Malawi Department of Social Welfare, and observation visits in the targeted districts. The approaches for collecting data mentioned were triangulated for the development of a baseline survey. The baseline survey generated systematically collected data of the experiences and recalls as well as the missing data from the preliminary evaluation of the existing data. The baseline data gave the Young Women's Christian Association (YWCA) insight on the type of intervention required in order to give a greater and more holistic effect on the beneficiaries. We also discuss the lessons we learned as to whether the assumptions we had made at the onset were correct. If they were not correct, we explained the measures we took to correct the design or implementation of the project. Finally, the data provided benchmarks for project monitoring and evaluation.